Impact of summer heat and mitigation strategies on apple (Cosmic Crisp®) fruit color dynamics quantified using crop physiology sensing system - Basavaraj R. Amogi; Lav R. Khot; Bernardita V. Sallato (Journal of Agriculture and Food Research)
Frequent summer heat waves significantly challenge global fruit production, including apples (Malus domestica Borkh.) grown in Washington State, USA. While growers employ heat mitigation strategies like evaporative cooling with overhead sprinklers, foggers, shade/drape netting, and protective sprays, these techniques can inadvertently compromise fruit coloration, a key quality attribute influencing harvest timing, marketability, and consumer acceptance. Thus, this study investigated whether continuous, in-orchard monitoring of fruit color and microclimatic conditions could help optimize mitigation practices without compromising fruit quality. Using a Crop Physiology Sensing System (CPSS), apple (Cosmic Crisp®) fruit color progression and ambient weather conditions were monitored at 5-min intervals throughout the 2022 growing season under fogging, netting, and untreated control treatments. CPSS with integrated RGB imaging data were contrasted with ambient air temperature (Tair) within each treatment using a custom developed algorithm. The algorithm allowed automated and daily quantification of fruit color metrics, including hue angle (h°), color transition from green to red (a∗), and chroma. Results suggest that prolonged daytime Tair exceeding 35 °C could cause significant degradation of red pigmentation (increasing h° and declining a∗). Netting caused overnight heat retention and delayed color recovery, whereas fogging effectively moderated the microclimate, preserving red coloration. Crucially, a nighttime drop in Tair to approximately 12 °C facilitated the reappearance of red coloration. To our knowledge, this is the first study to document both the degradation and subsequent reappearance of apple fruit coloration under field conditions. These findings suggest that continuous apple fruit color and ambient air temperature monitoring could be useful to effectively employ heat mitigation techniques, thereby improving fruit quality and market value at harvest.